Preservation of fungi and actinomycetes in distilled water - Rodrigues, Elaine G. (1992)
Several methods have been used for the preservation of fungi, all of them presenting advantages and disadvantages. The choice of the methods depends upon the laboratory availabilities, time of preservation, genetic stability of the cultures and other factors. In this work the results obtained through the utilization of Castellani's method (preservation in distilled water) for the maintenance of 174 strains belonging to the "Micoteca do Instituto de Medicina Tropical de São Paulo" are presented. These strains were analyzed after 6, 12, 18 and 24 months, with regard to the percentage of viability taking into consideration the rates of growth and contamination. The smallest percentage of viability occurred in the group of the actinomycetes (50 to 100%) and the largest one in the group of the yeasts (near 100%). According to other authors, the Castellani's method, besides being simple and economically feasible for small size laboratories, yields good results